2023
DOI: 10.1021/acsorginorgau.3c00013
|View full text |Cite
|
Sign up to set email alerts
|

Long-Range Kinetic Effects on the Alternating Ring Opening Metathesis of Bicyclo[4.2.0]oct-6-ene-7-carboxamides and Cyclohexene

Abstract: We report an investigation of rates of ruthenium-catalyzed alternating ring opening metathesis (AROM) of cyclohexene with two different Ru-cyclohexylidene carbenes derived from bicyclo[4.2.0]oct-6-ene-7-carboxamides (A monomer) that bear different side chains. These monomers are propylbicyclo[4.2.0]oct-6-ene-7-carboxamide and N-(2-(2-ethoxyethoxy)ethanylbicyclo[4.2.0]oct-6-ene-7-carboxamide. The amide substitution of these monomers directly affects both the rate of the bicyclo[4.2.0]oct-6-ene-7-carboxamide rin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Despite previous accomplishments in synthesizing long, alternating AB copolymers with large molecular weights, , the highest degree of polymerization that could be achieved for the [4.2.0] glycopolymers was 50 AB units. The presence of sugar moieties on bicyclo[4.2.0]oct-6-ene-7-carboxamide seemed to significantly lower the reactivity of the reaction, most likely due to steric hindrance as suggested by previous studies. , Despite allowing the reaction to run for longer than 20 h, copolymers significantly longer than 50 AB units could not be achieved. We have previously demonstrated that polynorbornene 100-mers displaying mannose and fucose efficiently induce AE in mouse sperm and polynorbornene 50-mers display the same number of ligands as the [4.2.0] glycopolymers.…”
Section: Resultsmentioning
confidence: 75%
“…Despite previous accomplishments in synthesizing long, alternating AB copolymers with large molecular weights, , the highest degree of polymerization that could be achieved for the [4.2.0] glycopolymers was 50 AB units. The presence of sugar moieties on bicyclo[4.2.0]oct-6-ene-7-carboxamide seemed to significantly lower the reactivity of the reaction, most likely due to steric hindrance as suggested by previous studies. , Despite allowing the reaction to run for longer than 20 h, copolymers significantly longer than 50 AB units could not be achieved. We have previously demonstrated that polynorbornene 100-mers displaying mannose and fucose efficiently induce AE in mouse sperm and polynorbornene 50-mers display the same number of ligands as the [4.2.0] glycopolymers.…”
Section: Resultsmentioning
confidence: 75%